Pharmacological Potential and Bioactivity of Pandanus spp.: A Scopus-Based Bibliometric Analysis - Setiyoputro, Aji; Samodra, Galih; Prabandari, Rani (Pharmacogenius Journal, 2025)
ntroduction: Pandanus spp. are tropical plants widely recognized for their ethnomedicinal use and diverse phytochemical constituents, including flavonoids, alkaloids, and phenolic compounds with pharmacological potential. Despite this, global research on Pandanus remains fragmented and lacks systematic mapping. Objective: This study aimed to perform a bibliometric analysis of Pandanus research related to pharmacological potential and bioactivity using Scopus-indexed literature. Method: A Scopus search was conducted using taxonomic and pharmacological keywords without time restrictions, limited to English-language articles, reviews, and conference papers. Eligible records were analyzed with Bibliometrix (Biblioshiny) for bibliometric indicators and VOSviewer for visualization. Metrics included publication trends, citations, authorship, institutional and country contributions, co-citation networks, and keyword co-occurrence. Conclusion: Between 1984–2024, publications exhibited steady growth, with early studies maintaining citation relevance for decades. Productivity was concentrated among a few authors, notably Nonato MG, supported by institutions such as Universiti Malaysia Terengganu and other Southeast Asian universities. Collaboration networks were primarily Asia-centered, with Indonesia and India as key hubs. Keyword mapping revealed four thematic clusters: phytochemistry and antioxidants, taxonomy and isolation, pharmacology and metabolism, and ethnomedicine. The Journal of Ethnopharmacology emerged as the primary publication outlet. Pandanus research reflects sustained interest, regional leadership, and thematic diversity. Broader international collaborations and advanced pharmacological investigations are essential to fully realize the therapeutic promise of Pandanus-derived compounds.